Correlation between Cornification of Vaginal Epithelial Cells and Serum Progesterone Concentration during Proestrus and Estrus in She-Dogs - Sharma, Ananya; Singh, Madhumeet; Sharma , Akshay (The Indian Journal of Animal Reproduction, 2022)
The present study was conducted on fifteen she-dogs presented to the Department of Veterinary Gynaecology and Obstetrics, CSK Himachal Pradesh Krishi Vishvavidyalaya (CSKHPKV), Palampur for determination of mating time. Serum progesterone was estimated from the blood sample collected in the clot activator by cephalic venepuncture from she-dogs during the proestrus and estrus stages. The objective of the study was to establish a correlation between epithelial cells proportion (%) in vaginal epithelium with serum progesterone concentration (ng/mL) during proestrus, early estrus, and mid to late estrus in she-dogs. A significant positive correlation (r= 0.74; p<0.01) between cornified cells and progesterone concentration was recorded during mid to late estrus whereas the correlation was non-significantly negative (p>0.05) for non-cornified cells (r= -0.7408 to -0.5807). Also, the cornified cell proportion was significantly higher (p<0.01) during mid to late estrus as compared to proestrus and early estrus. In conclusion, the present study validated the statistical association between cornified vaginal epithelial cells and serum progesterone concentration during mid to late estrus.